2009
DOI: 10.1063/1.3124187
|View full text |Cite
|
Sign up to set email alerts
|

Linking microscopic guest properties to macroscopic observables in clathrate hydrates: Guest-host hydrogen bonding

Abstract: Molecular dynamics simulations are used to compare microscopic structures and guest dynamics to macroscopic properties in structure II clathrate hydrates with cyclopentane, tetrahydrofuran (THF), 1,3-dioxolane, tetrahydropyran (THP), and p-dioxane as guests. Significant differences are observed between structural parameters and rotational dynamics for the different guests. The simulations show the formation of guest-host hydrogen bonds between the ether oxygen atoms of THF and THP and the cage water hydrogen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
171
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(187 citation statements)
references
References 40 publications
15
171
1
Order By: Relevance
“…The hydrogen bonds affect the clathrate hydrate structure and the dynamics of guest and host water molecules. It was observed in the study 9 that the oxygen atoms of 1,3-dioxolane (DIO) does not form hydrogen bonds with the large cage water molecules. As temperature increases, the probability of hydrogen bonds between the guest and the host water molecules can either decrease or increase depending on the guest 11 , whereas it is expected that the stability of clathrate decreases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen bonds affect the clathrate hydrate structure and the dynamics of guest and host water molecules. It was observed in the study 9 that the oxygen atoms of 1,3-dioxolane (DIO) does not form hydrogen bonds with the large cage water molecules. As temperature increases, the probability of hydrogen bonds between the guest and the host water molecules can either decrease or increase depending on the guest 11 , whereas it is expected that the stability of clathrate decreases.…”
Section: Discussionmentioning
confidence: 99%
“…The relaxation contribution to the Helmholtz free energy difference has been derived in paper 12 (9) where the Hamiltonian α H of the double-size system of the relaxation stage depends of the translational constraint rˆ and the orientational constraints ηˆ and κˆ, Putting the replication and relaxation free energy contributions (6) and (9) together gives the Helmholtz free energy per particle of a general molecular crystal (10) have been found for all cases discussed here. …”
Section: Free Energy Calculations Of Empty and Fully Occupied Clatmentioning
confidence: 92%
“…56 However, in the case of THF hydrate the MD simulations showed that these H-bonds are rather short lived (0.28 ps at 200 K), and thus no effects on the structure can be detected. 53 This injection of L-defects by the guest appears to be quite a different process from the propagation of Bjerrum defects, which governs the water reorientation process as observed by dielectric and NMR relaxation. 10,15 For instance, for THF hydrate the activation energy for L-defect injection was found to be ∼8.3 kJ/mol from MD simulation, 53 compared with an experimental value of ∼30 kJ/mol for defect propagation (see refs.…”
Section: Comparison Of Experimental and Simulated Lineshapes In The Ementioning
confidence: 99%
“…10,15 Recent molecular dynamics (MD) simulation studies on nanosecond timescales have in fact observed the existence of both transient and persistent guest-host hydrogen bonds for oxygencontaining guests [53][54][55] . In the simplest cases, this corresponds exactly to the injection of an L-defect as there is indeed a misdirected H-bond, leaving a hydrogen vacancy in the water lattice.…”
Section: Comparison Of Experimental and Simulated Lineshapes In The Ementioning
confidence: 99%
“…Recent structural analysis and molecular simulations have shown that some guest molecules which form strong hydrogen bonds with the water framework of the clathrate hydrate lattice may nonetheless produce stable phases (20)(21)(22)(23). It is therefore reasonable to consider that ammonia has potential as a clathrate guest molecule.…”
mentioning
confidence: 99%